Reformasi dan Theologi Reformed: Reformasi dan Theology Reformed - Aritonang, Arthur (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
The book by Rev. Stephen Tong discusses Reformation History and Reformed theology. The questions presented in this book are as follows: Why did Martin Luther need to reform? What is the uniqueness of Reformed theology? What is Augustine's contribution to the thought of Luther and Calvin? Fourth, how is the relevance of Reformed theology for the Church and Society? The results of this study are first, the Roman Catholic churches at that time had deviated or were no longer by the Bible such as increasing corruption in the church and the sale of letters of absolution. According to Martin Luther, these changes can only be corrected if the doctrine is returned to the Bible. Secondly, the concept of predestination is that only God's chosen will be saved; the next is church discipline. The Reformed Church is disciplined when congregation members commit acts against the gospel. Third, Augustinus' influence on Luther's thinking is that we are justified by faith, while for Calvin it is the sovereignty of God and His Grace. Fourth, for the Church, the concept of the Trinity, Christ is the only mediator, the Holy Spirit is Himself God and the Bible is the revealed Word of God.